Investigating the Effect of Direct Touch Method on Insulator Replacement in Candra Asri Feeder - Pancane, I Wayan Dikse (PT FORMOSA CENDEKIA GLOBAL, 2024)
PLN UP3 East Bali in carrying out Fulcrum Insulator maintenance chooses to use Work In Direct Touch Voltage status. The purpose of using this method is to reduce the value of reliability indices in the form of System Averange Interruption Duration Index, System Averange Interruption Frequency Index, and Saving kWh which results in rupiah savings. The results showed that in 11 times the replacement work of the Fulcrum Insulator extinguishing method resulted in a SAIDI value of 0.105 minutes per customer, SAIFI of 0.104 times per customer. Meanwhile, if done with the Direct Touch method, PDKB gets a SAIDI and SAIFI value of 0. So if done with the Direct Touch Method, PDKB gets embedded 32,903.67 kWh and Rp. 42,248,314.85